2012
DOI: 10.1177/1074248412458975
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Inhibition Attenuates Myocardial Damage, Adverse Remodeling, and Dysfunction During Fulminant Myocarditis in the Rat

Abstract: Background Myocarditis is a life-threatening heart disease characterized by myocardial inflammation, necrosis and chronic fibrosis. While mast cell inhibition has been suggested to prevents fibrosis in rat myocarditis, little is known about its effectiveness in attenuating cardiac remodeling and dysfunction in myocarditis. Thus, we sought to test the hypothesis that mast cell inhibition will attenuate the inflammatory reaction and associated left ventricular (LV) remodeling and dysfunction after fulminant auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Although found mainly in the skin, gastrointestinal tract, and airways, they are known to reside in cardiac tissue and have been shown to play a key role in the pathogenesis of HF (Mina et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although found mainly in the skin, gastrointestinal tract, and airways, they are known to reside in cardiac tissue and have been shown to play a key role in the pathogenesis of HF (Mina et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mast cells have been implicated in the pathogenesis of HF and play a critical role in the fibrotic response to infectious and inflammatory stimuli (Matsumori et al 1994). Although found mainly in the skin, gastrointestinal tract, and airways, they are known to reside in cardiac tissue and have been shown to play a key role in the pathogenesis of HF (Mina et al 2013). Consistent with the enhanced inflammatory response in the TAC mice compared to their WT counterparts, we also found a striking increase in both interstitial and perivascular fibrosis in the PO hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Palaniyandi et al [ 19 ] demonstrated that the MC stabilizer disodium cromoglycate (also known as cromolyn) could dramatically reduce fibrosis in a model of myocarditis, whereby rats were injected with porcine cardiac myosin emulsified with complete freund’s adjuvant with Mycobacterium tuberculosis H37RA. A subsequent study confirmed the anti-fibrotic effect of cromolyn in myocarditis in rats [ 22 ]. We provided the first causal evidence that MCs play a role in cardiac fibrosis in the hypertensive heart [ 23 ].…”
Section: Evidence For the Causal Involvement Of Mast Cells In Cardmentioning
confidence: 81%
“…119 Consequently, stabilizing mast cells using disodium cromoglycate prevented left ventricular dilatation, attenuated left ventricular dysfunction, and reduced myocardial fibrosis compared with controls. In aortocaval fistula-induced internal expansion of the left ventricle in mice, a deficiency of the mast-cell activators substance P and neurokinin-1 reduced left ventricular expansion by nearly eightfold, as well as significantly reducing MMP activity and myocardial collagen degradation.…”
Section: Myocardial Remodellingmentioning
confidence: 99%